Pleiotropy of Glycogen Synthase Kinase-3 Inhibition by CHIR99021 Promotes Self-Renewal of Embryonic Stem Cells from Refractory Mouse Strains - Ye, Shoudong; Tan, Li; Yang, Rongqing; Fang, Bo; Qu, Su; Schulze, Eric N.; Song, Houyan; Ying, Qilong; Li, Ping (PLOS ONE, 2012)
Background Inhibition of glycogen synthase kinase-3 (GSK-3) improves the efficiency of embryonic stem (ES) cell derivation from various strains of mice and rats, as well as dramatically promotes ES cell self-renewal potential. β-catenin has been reported to be involved in the maintenance of self-renewal of ES cells through TCF dependent and independent pathway. But the intrinsic difference between ES cell lines from different species and strains has not been characterized. Here, we dissect the mechanism of GSK-3 inhibition by CHIR99021 in mouse ES cells from refractory mouse strains. Methodology/Principal Findings We found that CHIR99021, a GSK-3 specific inhibitor, promotes self-renewal of ES cells from recalcitrant C57BL/6 (B6) and BALB/c mouse strains through stabilization of β-catenin and c-Myc protein levels. Stabilized β-catenin promoted ES self-renewal through two mechanisms. First, β-catenin translocated into the nucleus to maintain stem cell pluripotency in a lymphoid-enhancing factor/T-cell factor–independent manner. Second, β-catenin binds plasma membrane-localized E-cadherin, which ensures a compact, spherical morphology, a hallmark of ES cells. Further, elevated c-Myc protein levels did not contribute significantly to CH-mediated ES cell self-renewal. Instead, the role of c-Myc is dependent on its transformation activity and can be replaced by N-Myc but not L-Myc. β-catenin and c-Myc have similar effects on ES cells derived from both B6 and BALB/c mice. Conclusions/Significance Our data demonstrated that GSK-3 inhibition by CH promotes self-renewal of mouse ES cells with non-permissive genetic backgrounds by regulation of multiple signaling pathways. These findings would be useful to improve the availability of normally non-permissive mouse strains as research tools.